2010
DOI: 10.1097/jto.0b013e3181d95dd4
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of BI 2536, a Novel Plk-1 Inhibitor, in Patients with Stage IIIB/IV Non-small Cell Lung Cancer Who Had Relapsed after, or Failed, Chemotherapy: Results from an Open-Label, Randomized Phase II Clinical Trial

Abstract: BI 2536 monotherapy has modest efficacy and favorable safety in relapsed non-small cell lung cancer. The findings support the further development of polo-like kinase-1 inhibitors within this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 26 publications
(35 reference statements)
8
81
0
3
Order By: Relevance
“…In phase I, dose-escalation and pharmacokinetic studies of BI 2536 in patients with advanced solid tumors, the maximum tolerated dose was 200 mg, which would produce an estimated tissue concentration of approximately 10 mM (consistent with the measured plasma concentrations of 1À10 mM) [17]. BI 2536 is currently in phase II/III clinical studies, although this is not the only Plk1 inhibitor under development.…”
Section: Discussionmentioning
confidence: 77%
“…In phase I, dose-escalation and pharmacokinetic studies of BI 2536 in patients with advanced solid tumors, the maximum tolerated dose was 200 mg, which would produce an estimated tissue concentration of approximately 10 mM (consistent with the measured plasma concentrations of 1À10 mM) [17]. BI 2536 is currently in phase II/III clinical studies, although this is not the only Plk1 inhibitor under development.…”
Section: Discussionmentioning
confidence: 77%
“…Although a number of other compounds that target the Plk pathway are under investigation [8][9][10] , BI 2536 is the first selective member of the Plk1 inhibitor class to have begun clinical trials, wherein it has been evaluated in the treatment of patients with solid tumours, including metastatic or advanced pancreatic cancer 21 , prostate cancer 22 , and nsclc [as monotherapy 23 and in combination with pemetrexed 24 ]. Although antitumour efficacy has been noted in individual patients in these clinical trials, overall antitumour activity-in terms of response rate, duration of response, clinical benefit, and progressionfree survival-was disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that BI-2536 has potent tumoricidal activity against cancer cells, particularly those harboring mutations in TP53 (44-47). BI-2536 was the subject of several clinical trials in patients with cancers of the lung, breast, ovaries, and uterus (48)(49)(50)(51)(52)(53). Although it showed evidence of efficacy in cancer patients, its development was abandoned after phase II trials revealed unacceptable toxicity (grade 4 neutropenia) at subtherapeutic doses.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hymentioning
confidence: 99%